Reclaiming his ruined princess - Crews, Caitlin (Harlequin presents, 2022)
"When Amalia Montaigne discovers she's not the Crown Princess everyone thought she was, she craves solitude. The Spanish island where she had an illicit taste of freedom seems perfect. Until she realizes billionaire Joaquin Vargas is also in residence...and still devastatingly smoldering! Joaquin never forgot the princess who left their chemistry behind. As for forgiveness? Impossible! Hardened by his childhood of abandonment, he's determined this time to claim then leave her. But Joaquin didn't count on the passion exploding between them--insatiable, inescapable and strong enough to ruin them both..." -- Page [4] cover.